Cost of narrowband ultraviolet B for psoriasis. (1st November 2018) - Boswell, K.; Cameron, H.; West, J.; Fleming, C.; Ibbotson, S.; Dawe, R.; Foerster, J.
Summary: Psoriasis is a very common disease, affecting around 2% of people worldwide and 1.5 million in the UK. Many patients are affected throughout their lives. Psoriasis can often be treated with creams. However, when this is not enough patients can be treated by specially filtered ultraviolet light called "narrowband‐UVB". This treatment is very effective in 3 out of 4 people, safe, and does not require blood testing. However, in many regions it is not readily available. One reason for this is that it is regarded as expensive since patients have to attend 3 times per week for a few minutes for several weeks, and staff administer the treatment. In this study, the authors extracted all the treatment cost that one large provider in the UK, NHS Tayside, has incurred over six years for this treatment. Including even all indirect costs such as pension contribution, estate etc., NHS Tayside spent an average of only £257 per person for a complete treatment. This result suggests that offering this treatment to more patients would be very cost effective and might avoid or delay the need to use immunosuppressive drugs in many patients.